Assessment of radiation safety in cardiac CT angiography. Issue 51 (December 2017) - Lee, Yuan-Hao; Chang, Po-Yen; Tay, Shee Yen; Tsai, Cheng-Yu; Cheng, Po-Hsin; Lao, Wilson T.; Chan, Wing P.
Abstract : Abstract: This study investigates the radiation dose and image quality of patients not receiving β-blockers for cardiac CT angiography (CCTA) with or without the optimization of electrocardiographic (ECG) pulsing window. The differences in patient characteristics are also characterized. Normal-weight and obese patients (n = 154) with heart rates between 65 and 80 beats per minutes (bpm) during the prospective axial scanning were enrolled retrospectively. The ECG pulsing windows were set at 50% to 75% (Group A) or 60% to 75% (Group B) of the R-R interval for patients with heart rate variability higher than or not exceeding ±5 bpm, respectively. The effective doses of individual patient were estimated from the dose length product of the CCTA scan. Two radiologists independently reviewed the images and applied a 4-point Likert scale for image quality assessment. The patients' characteristics were compared along with the patients' effective doses between groups. The optimized pulsing window significantly reduced the average radiation dose for normal-weight and obese patients by 33% and 27%, respectively. The CCTA image quality of patients in Group A was not different overall from those obtained from Group B. Nondiabetic obese patients were more likely to be accepted for the use of the optimized pulsing window. Unlike obese patients, normal-weight patients revealed no characteristic difference between Groups A and B. This study indicates an equivalent efficacy of using optimized pulsing windows for reducing the radiation dose for patients without β-blocker administration between different body weight groups. Nevertheless, gender and diabetic status became prominent characteristics in the obese group when matching up with the optimized pulsing window.